Impact of Financial Risk Factors on Profitability of Nepalese Commercial Banks - Uprety, Ajit (Nepalese Journal of Business, 2024)
The study examines the impact of financial risk factors on profitability of Nepalese commercial banks. Return on assets and net interest margin are selected as the dependent variables. The selected independent variables are non-performing loan, capital adequacy ratio, loan to deposit ratio, cash reserve ratio, operating cost ratio and exchange rate. The study is based on secondary data of 14 commercial banks with 112 observations for the period from 2014/15 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of financial risk factors on profitability of Nepalese commercial banks. The study showed that non-performing loan has a negative impact on return on assets and net interest margin. It shows that increase in non-performing loan leads to decrease in return on assets and net interest margin. On the other hand, capital adequacy ratio has a positive impact on return on assets and net interest margin. It implies that increase in capital adequacy ratio leads to increase in return on assets and net interest margin. Similarly, loan to deposit ratio has a negative impact on return on assets and net interest margin. It implies that increase in loan to deposit ratio leads to decrease in return on assets and net interest margin. However, cash reserve ratio has a positive impact on return on assets and net interest margin. It means increase in cash reserve ratio leads to increase in return on assets and net interest margin. In addition, BOPO ratio has a negative impact on return on assets and net interest margin. It means that increase in BOPO ratio leads to decrease in return on assets and net interest margin. Moreover, exchange rate has a negative impact on return on assets and net interest margin. It means that increase in exchange rate leads to decrease in return on assets and net interest margin.